Fenomenologi Sosial Kehidupan Beragama di Desa Sodong - Mardotillah Aulia Nur Rahmah; Ahmad Ridho (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This research is to deeply analyze and describe the social interaction patterns of the Sodong Village community in their religious life through a phenomenological approach. Phenomenology is a method for understanding the essence of a phenomenon consciously experienced by individuals, in this case, how the Sodong Village community lives their social and religious lives. This study uses a qualitative-descriptive approach with data collection techniques such as participatory observation and in-depth interviews with religious figures, community leaders, and residents. The results of this study reveal that the social interactions of the Sodong Village community are divided into three main patterns: interactions that are communal and social, religious interactions, and educational interactions. These patterns not only serve as a social mechanism to maintain harmony but also as a medium to strengthen religious and local cultural identity. The findings conclude that daily social interactions, based on the values of tolerance and mutual respect, are the primary foundation for the harmony of religious life in Sodong Village.